Cathay & Southwest: flying the flag of good practice in airline mergers. Issue 8 (13th July 2015) - Mark Thomas, Mr; Sharma, Reetesh; Thomas, Mark
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This article highlights the essential factors to be considered for successful mergers and acquisitions (M & As) in the aviation industry. The article draws insights from the successful deals between Morris and Southwest Airlines as well as Cathay Pacific and Dragonair. Design/methodology/approach – The article is a case study of two successful mergers in the airline industry, one in the USA and one in Asia. Findings – M & As in the airline industry are loaded with difficulties. These include problems of brand identification, opposition from key stakeholders and the need of forming one coherent organisational culture. However, this does not mean that they are impossible. Two large-scale mergers have shown that successful mergers can occur in the industry. Originality/value – This article gives examples of two successful M & A deals from the aviation industry and shows the important factors to achieve this.